Cellular automata on high-dimensional hypercubes - Brunnet, Leonardo Gregory (2004)
The emergence of nontrivial collective behavior is studied in large families of cellular automata rules implemented on high-dimensional hypercubes. Evidence is found that the region of rule space where such macroscopic dynamics exists is well-defined in the infinite-dimension limit.